Form and Strategy: Three Urban Design Learning Experiences for Intermediate Cities (EAAE Annual Conference Proceedings, 2025)
To what scale can the architect’s design operate today? This paper presents the outcomes of recent teaching experiences carried out in intermediate cities in Catalonia, contexts where conceiving the city as a project is still a field of work for architects, and where it is essential to explore new ways of planning amidst an increasingly dynamic and complex context. These experiences stem from the final- year urban design studios of the architecture program at ETSAB, which focus on the development of complex urban and territorial projects.The paper shares three pedagogical approaches focused on redesigning the urban backgrounds of intermediate cities. These are hidden, vacant, or expectant areas behind the dominant ‘figure’ of the city, where the biophysical ground remains evident and which can be strategic in providing coherence and cohesion to urban form. The first approach explores an inverted scalar method, beginning with small, singular fragments and leading to strategic planning: from form to systems. The second emphasizes experiential read- ings of these spaces through walking and immersion, helping students sense their beauty and potential in person. Thethird centers on learning from references using cardboard study models, allowing students to grasp spatial qualities by touching, rebuilding and comparing valuable urban projects.The paper concludes with a reflection on the role of urbanists in the improvement of intermediate cities, empha- sizing the need for an approach that integrates a renewed appreciation of the long-tradition of artisanal skills inurban design with a more strategic vision aimed at guiding open-processes.Aureli, Pier Vittorio, ed. The city as a project. Berlin: Ruby Press, 2013.Clua, Álvaro, ed. Urban Backgrounds. Projects for the green belt of Igualada. Barcelona: Laboratori d’Urbanisme de Barcelona, 2023.De Solà-Morales, Manuel, et al. El Projecte Urbà: Una Experiència Docent. Barcelona: UPC, 1999.Juel-Christiansen, Carsten, ed. Transitions. Space in the Dispersed City. København: The Architectural Magazine, 2000.Parcerisa, Josep. Forma Urbis: Cinco ciudades bajo sospecha. Barcelona: LUB, 2012.Parcerisa, Josep, and Carles Crosas, eds. Barcelona Enllaços. Barcelona:LUB, 2013.Riboulet, Pierre. ‘La Ville Comme Oeuvre’. In Conférences Paris d’architectes. Paris: Pavillon de l’Arsenal, 1994.Russo, Michelangelo, et al. Transitional Landscapes. Macerata: Quodlibet, 2023.